China at large, Chinas for comparative conversation: a commentary on "Urbanizing dynamics of global China". Issue 10 (26th November 2022) - Bunnell, Tim
ABSTRACT: This commentary brings diverse and dispersed urban geography analyzes of global China into conversation. I show that findings from the pre-COVID-19 research presented in the four articles that comprise the special issue on Urbanizing Dynamics of Global China beg comparative questions of each other, both retrospective and future-facing. My hope is that the collection of articles will thus provide grounds for new comparative, and perhaps collaborative, research across urban Chinas that have previously been examined separately.